INSPEKSI SANITASI LINGKUNGAN PERUMAHAN DI PERUMAHAN TAMAN SURYA AGUNG, WAGE, TAMAN, SIDOARJO - Jesika Margareta; Dhanti Prima D; Theresia Adriana E.D.W; Rizky Puspitarini (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
A house is a basic human need both as a place to live and as an investment asset. A healthy house is one of the means to achieve optimal health. The realization of public health in a housing is determined by the location, quality of environmental health infrastructure. The purpose of this research is to inspect and assess the quality of environmental sanitation in the Taman Surya Agung Sidoarjo housing estate, with reference Kepmenkes RI No. 829/1999 on Housing Health Requirements, SNI 03-1733-2004 on environmental management procedures, and Permenkes No. 3/2014 on Community-Based Total Sanitation. The research method is descriptive analytic by conducting direct observations and interviews in the field at three houses located in Taman Surya Agung Housing. The instrument used is an environmental health inspection form. The results showed that there were several variables that did not meet the requirements for the housing variable, house components, occupant behavior and house sanitation, but of all the houses inspected, they were categorized as healthy houses with an average value of 88.5%. The conclusion of this study is the residential and residential environment in Taman Surya Agung Sidoarjo Housing is categorized as a healthy environment.